Clinical Outcome and Striatal Dopaminergic Function After Shunt Surgery in Patients With Idiopathic Normal Pressure Hydrocephalus. (8th June 2021) - Todisco, Massimiliano; Zangaglia, Roberta; Minafra, Brigida; Pisano, Patrizia; Trifirò, Giuseppe; Bossert, Irene; Pozzi, Nicoló Gabriele; Brumberg, Joachim; Ceravolo, Roberto; Isaias, Ioannis Ugo; Fasano, Alfonso; Pacchetti, Claudio
Abstract : Objective: To determine changes in clinical features and striatal dopamine reuptake transporter (DAT) density after shunt surgery in patients with idiopathic normal pressure hydrocephalus (iNPH). Methods: Participants with probable iNPH were assessed at baseline by means of clinical rating scales, brain MRI, and SPECT with [ 123 I]-N-ω-fluoropropyl-2β-carbomethoxy-3β-(4-iodophenyl)nortropane (FP-CIT). Levodopa responsiveness was also evaluated. Patients who did or did not undergo lumboperitoneal shunt were clinically followed up and repeated SPECT after 2 years. Results: We enrolled 115 patients with iNPH. Of 102 patients without significant levodopa response and no signs of atypical parkinsonism, 92 underwent FP-CIT SPECT (58 also at follow-up) and 59 underwent surgery. We identified a disequilibrium subtype (phenotype 1) and a locomotor subtype (phenotype 2) of higher-level gait disorder. Gait impairment correlated with caudate DAT density in both phenotypes, whereas parkinsonian signs correlated with putamen and caudate DAT binding in patients with phenotype 2, who showed more severe symptoms and lower striatal DAT density. Gait and caudate DAT binding improved in both phenotypes after surgery ( p < 0.01). Parkinsonism and putamen DAT density improved in shunted patients with phenotype 2 ( p < 0.001). Conversely, gait, parkinsonian signs, and striatal DAT binding worsened in patients who declined surgery ( p < 0.01). Conclusions: This prospective interventional study highlights the pathophysiologic relevance of striatal dopaminergic dysfunction in the motor phenotypic expression of iNPH. Absence of levodopa responsiveness, shunt-responsive parkinsonism, and postsurgery improvement of striatal DAT density are findings that corroborate the notion of a reversible striatal dysfunction in a subset of patients with iNPH.